Al-Ikhtibaar Limahaarat al-Qira'ah Fii Ta'liim al-Lughat al-'Arabiyyat - Gautama Veri Vetiana; Alfy Mamduh Nuruddin (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2021)
The evaluation in learning process is an essential tool in the educational, and we couldn’t do without it. Carry out this evaluation in order to get input or update in the process and educational goals. Student learning outcomes are not limited to cognitives aspect, but also includes three aspect such cognitive, emotional and psychological which the teacher is evaluating these aspect. In the evaluation process, teachers are expected to understand the reality of learning and its results and classify the result, even evaluation tools. One such tool is a test. This test is held to evaluate the student an defind out the extent of his mastery, the extent of his progress and where he is in relation to his peers, This test has different types, its use varies according to needs and situation. Among these tests is the reading test, this test requires student proficiency in reading comprehension to answer the following questions. Therefore, have to teacher understands the steps in developing the test properly to achieve the desired goals in the evaluation process.